2011
DOI: 10.1590/s2179-975x2011000200004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbofuran and metsulfuron-methyl on the benthic macroinvertebrate community in flooded ricefields

Abstract: AIM: This study evaluated the effect of the insecticide carbofuran and the herbicide metsulfuron-methyl on the abundance and diversity of benthic macroinvertebrates in a paddy ricefield. METHODS: To achieve this goal, two pesticide treatments [the insecticide carbofuran (IC) and the herbicide metsulfuron-methyl (HM)] and a control (Co) treatment with no added pesticide were established in an experimental area of the Plant Science Department of the Federal University of Santa Maria. Soil samples were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Dissolved oxygen concentration remained quite low in the analyzed treatments, likely due to low water depth (15 cm). Other authors also reported low dissolved oxygen concentration in areas planted with rice and subjected to pesticide applications (GOLOMBIESKI et al, 2008;REIMCHE et al, 2008;BAUMART et al, 2011). 2003;DI GIOVANNI et al, 1996).…”
Section: Biotic Datamentioning
confidence: 95%
“…Dissolved oxygen concentration remained quite low in the analyzed treatments, likely due to low water depth (15 cm). Other authors also reported low dissolved oxygen concentration in areas planted with rice and subjected to pesticide applications (GOLOMBIESKI et al, 2008;REIMCHE et al, 2008;BAUMART et al, 2011). 2003;DI GIOVANNI et al, 1996).…”
Section: Biotic Datamentioning
confidence: 95%
“…A less significant degradation pathway of carbofuran is through the photolysis reaction. Carbofuran is not likely to accumulate in sunlight-exposed water and does not bioaccumulate (Baumart et al, 2011). The metabolic product of photolysis includes (Evert, 2002) 2,3-dihydro-2,2 dimethyl benzofuran-4,7-diol and 2,3-dihydro-3 keto-2,2 dimethyl benzofuran-7-yl carbamate (3-ketocarbofuran) (Mahalakshmi et al, 2007;Remucal, 2014).…”
Section: Photolysis Degradationmentioning
confidence: 99%
“…Rice crops in majority are inserted in lowland areas, areas located close to watercourses and ground water. In this sense, studies analyzing residues of pesticides in irrigation water are also relevant, since the contamination of water sources may occur as a result of management practices and extravasation of irrigation water (Rodrigues et al, 2013), may reflect negatively on water quality, and thus present health risks to non‐target organisms, such as zooplankton community (Golombieski et al, 2008), benthic macroinvertebrates (Mize et al, 2008; Baumart et al, 2011), fish (Hussar et al, 2004; Nakagome et al, 2007; Toni et al, 2011) and also interfere in the quality of drinking water (Narita et al, 2014).…”
mentioning
confidence: 99%